Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia terhadap Kemampuan Kognitif Materi KPK dan FPB - Witrayeni, Vivi; Arlis, Syamsu; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aimed to determine the effect of Indonesian realistic mathematics education approach to cognitive abilities of KPK and FPB fifth grade student of SD Negeri 09 Belakang Balok Bukittinggi. Type of research is experimental research with quasi experimental design. The sample of research are VA class and VB class students as much as 53 people. The results of research data used was obtained t t-test 2,126>2,008 t-table at a level of 0,05. Thus it can be concluded that there is a positive effect of Indonesian realistic mathematics education approach to abilities of KPK and FPB fifth grade student of SD Negeri 09 Belakang Balok Bukittinggi. In addition, the average posttest of students in the experimental class is 85,15 higher than the average posttest in the control class that is 75,70 Keyword: realistic mathematics education, cognitive ability